Optimized hybridized mathematical model for wastewater treatment and energy generation using microbial fuel cells. (October 2021) - Liu, Ruina; Lin, Youwei; Xu, Gongdi; Li, Yongfeng; Premalatha, R.; Chandran, Karthik
Abstract: In the current era of urbanization and industrialization, water pollution and energy generation are the main concerns in the climate change context. Microbial Fuel Cells (MFCs) utilize biodegradable carbon compounds in organic waste to produce an electric current.MFC technology provides sustainable solutions for renewable power systems and energy-efficient wastewater treatment for distributed electricity systems. However, in wastewater treatment, generating usable energy from the MFC remains a significant challenge for the system scale and implementation. Hence, in this paper, the Optimized Hybridized Mathematical Model (OHMM) has been proposed for wastewater treatment and energy generation using microbial fuel batteries. Furthermore, statistical analysis has a role in synthesizing knowledge of fuel cells, defining and limiting factors in electricity production. The findings show that the proposed OHMM method, Sensitivity Analysis, Uncertainty Analysis, and Accuracy reduces energy consumption and cost function compared to other existing methods. With more miniature steam, it reduces the amount of harmful smoke that power plants emit, preserves the natural resources of a planet, and protects habitats against destruction. They will lead to a healthier and happier world by taking action to reduce the battery.